PENETAPAN KADAR PIPERIN DALAM EKSTRAK BUAH LADA HITAM (Piper nigrum Linn.) MENGGUNAKAN LIQUID CHROMATOGRAPHY TANDEM MASS SPECTROMETRY (LC–MS/MS) - Alifia Putri Febriyanti; Siti Jazimah Iswarin; Susanti Susanti (Universitas Islam Bandung, 2018)
The utilization of medicinal plants have started growing rapidly in the world, including in Indonesia, along with the thinking back to nature, one of the plants that are often used as a medicine is black pepper fruit (Piper nigrum Linn.). Piperine is a major compound and potent substances contained in black pepper fruit as antidiarrheal activity. The aim of this study was to determine levels of piperine in 96% ethanol extract of black pepper fruit. The extraction method used Soxhlet in 96% ethanol as solvent. Analysis of piperine using qualitative analysis by thin layer chromatography (TLC) produces yellow stain after being sprayed by dragendorf and dark blue on observation Uv-Vis 365 nm with Rf extract value 0.49 and Rf piperine value 0.5. Quantitative analysis using LC – MS produces piperine levels at 26%. Before quantitative analysis, validation method needs to be done with the parameters, among others: linearity have regression equation y = has 1,981,691.1333x + 561,445.0000 and correlation coefficient (R2) of 0.9973, LOD and LOQ at 0.14 and 0.44 ppm, accuracy value (% recovery) between 95.90 – 100.77%, precision value (% KV) between 0.02 – 1.84%, and selectivity (RT) between 2.47 – 2.49. The results of the validation parameters are eligible so that piperine levels were obtained by LC – MS declared accurate, specific, and precise.